Pathogenic or Therapeutic: The Mediating Role of Gut Microbiota in Non-Communicable Diseases - Bu, Fan; Yao, Xingran; Lu, Zhihua; Yuan, Xiaomin; Chen, Chen; Li, Lu; Li, Youran; Jiang, Feng; Zhu, Lei; Shi, Guoping; Chen, Yugen (Frontiers in Cellular and Infection Microbiology, 2022)
Noncommunicable diseases (NCDs) lead to 41 million deaths every year and account for 71% of all deaths worldwide. Increasing evidence indicates that gut microbiota disorders are closely linked to the occurrence and development of diseases. The gut microbiota, as a potential transmission medium, could play a key role in the transmission and treatment of diseases. The gut microbiota makes noncommunicable diseases communicable. New methods of the prevention and treatment of these diseases could be further explored through the gut microbiota.